PWE-071 The management of small early rectal cancers—network MDT results. (28th May 2012) - Sheel, A R G; Titu, L; Skaife, P; Rooney, P S; Myint, S; ,
Abstract : Introduction: A regional Small and Early Rectal Cancer (SERC) MDT was established in 2008 with input from Gastroenterology, TEMS service, pathologists, oncologists, cancer specialist nurses and surgeons. All patients with stage 1 rectal cancer are referred, ensuring cases suitable for local excision (LE) are managed by teams with appropriate expertise in line with NICE guidance and peer review measures for colorectal cancer. 1 2 We aimed to review the outcome of patients managed by the MDT focusing on adequacy of treatment according to histology, follow-up and classical surgery. Methods: Observational study of the SERC MDT database. Results: The SERC MDT processed 137 referrals (62 f: 75 m. Median age 77 (range 36–90)). There were 48 malignant cases. Of 74 local excision (LE) procedures, 24 were performed for malignancy (see Abstract PWE-071 table 1 below for outcomes). Classical surgery was advised for nine patients. The stoma averse or surgically high-risk patients were offered direct radiotherapy (n=16). There were 14 attempted LE's prior to MDT referral. All were malignant and only three were completely excised. Incompletely excised lesions were referred for classical surgery or radiotherapy. Conclusion: This regional SERC MDT has demonstrated the successful implementation and functioning of the early rectal cancer MDT model. All small rectal lesions should be referred to MDT prior to attempt at LE, thus allowing for accurate staging and appropriate pre-operative planning. R0 resection rates need improvement. Competing interests: None declared. References: 1. Guidance on Cancer Services—Improving Outcomes in Colorectal Cancer: Manual Update . NICE, 2001. 2. Case Study: Implementing Early Rectal Cancer MDTs in Secondary Care . November 2011.